Exogenous abscisic acid prolongs the dormancy of recalcitrant seed of Panax notoginseng - Wang, Qing-Yan; Yang, Ling; Ge, Na; Jia, Jin-Shan; Huang, Rong-Mei; Chen, Cui; Meng, Zhen-Gui; Li, Long-Gen; Chen, Jun-Wen (Frontiers in Plant Science, 2023)
The seeds of Panax notoginseng (Burk.) F. H. Chen are typically characterized by their recalcitrance and after-ripening process and exhibit a high water content at harvest as well as a high susceptibility to dehydration. Storage difficulty and the low germination of recalcitrant seeds of P. notoginseng are known to cause an obstacle to agricultural production. In this study, the ratio of embryo to endosperm (Em/En) in abscisic acid (ABA) treatments (1 mg·l−1 and 10 mg·l−1, LA and HA) was 53.64% and 52.34%, respectively, which were lower than those in control check (CK) (61.98%) at 30 days of the after-ripening process (DAR). A total of 83.67% of seeds germinated in the CK, 49% of seeds germinated in the LA treatment, and 37.33% of seeds germinated in the HA treatment at 60 DAR. The ABA, gibberellin (GA), and auxin (IAA) levels were increased in the HA treatment at 0 DAR, while the jasmonic acid (JA) levels were decreased. ABA, IAA, and JA were increased, but GA was decreased with HA treatment at 30 DAR. A total of 4,742, 16,531, and 890 differentially expressed genes (DEGs) were identified between the HA-treated and CK groups, respectively, along with obvious enrichment in the ABA-regulated plant hormone pathway and the mitogen-activated protein kinase (MAPK) signaling pathway. The expression of pyracbactin resistance-like (PYL) and SNF1-related protein kinase subfamily 2 (SnRK2s) increased in the ABA-treated groups, whereas the expression of type 2C protein phosphatase (PP2C) decreased, both of which are related to the ABA signaling pathway. As a result of the changes in expression of these genes, increased ABA signaling and suppressed GA signaling could inhibit the growth of the embryo and the expansion of developmental space. Furthermore, our results demonstrated that MAPK signaling cascades might be involved in the amplification of hormone signaling. Meanwhile, our study uncovered that the exogenous hormone ABA could inhibit embryonic development, promote dormancy, and delay germination in recalcitrant seeds. These findings reveal the critical role of ABA in regulating the dormancy of recalcitrant seeds, and thereby provide a new insight into recalcitrant seeds in agricultural production and storage.